Peningkatan Efektivitas Pemasaran Jasa Perbankan Islam Melalui Pemahaman Terhadap Segmentasi Pelanggan - Yusuf, Burhanuddin (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2013)
There are three segments of customers in Islamic banking industry: business customers, rational customers, and religious customers. This study found that the levels of customer’s satisfaction/dissatisfaction at the three segments (business,rational, and religious traveler) were differentiating by customers’ perception of service quality. The business customers has a higher focus on service quality and on time performance factors. In addition, the profit sharing factor is the differentiating variable in the level of satisfaction/dissatisfaction for rational customers. The application of sharia principles is the differen-tiating variabel of religious segments.DOI: 10.15408/aiq.v5i2.2564